Self-medication in a Portuguese Urban Population: A Prevalence Study - AP Martins; AC Miranda; Z Mendes; MA Soares; AP Ferreira; A Nogueira; MA Soares (Formifarma, LDA., 2019)
Purpose To determine the prevalence of self-medication in a Portuguese urban population. To assess the feasibility of performing these studies in community pharmacies. Methods A cross-sectional study was chosen to collect information about demography, use of health services and drug utilization in a sample of pharmacy user-purchasers in a pre-determined period of time. Results The proportion of pharmacies which participated in the study was 18.3% (11 from 60 invited) in Lisbon and 37.5% (15 of 40 invited) in Porto. Among the 3312 selected patients, only 2.6% (n = 114) refused to participate. The prevalence of self-medication was found to be 26.2%. The distribution of self-medication by gender was 28.4% for males and 25.2% for females. Use of self-medication was statistically significantly higher (p < 0.001) among individuals aged between 10 and 49 years. The main therapeutic groups used for self-medication, according to the ATC classification, were throat preparations, cough and cold preparations, stomatological preparations (antiinfectives and corticosteroides for local oral treatment), laxatives, analgesics, dermatological preparations, vitamins, mineral supplements and other alimentary tract and metabolism products. Conclusions In the urban areas under study the overall prevalence of self-medication was 26.2%. Predictive factors for self-medication seem to be, a high level of education, professional status and length of waiting times for a medical consultation in cases of a severe health problem. Further research on this subject is needed to confirm the reproducibility of these results, since potential selection bias could have been introduced due to the method used for patient selection. Pharmacoepidemiologic research is feasible in Portuguese community pharmacies. Published in: Pharmacoepidemiol Drug Saf. 2002; 11: 409-14.